The Determinants of Foreign Direct Investment in Brazil - Eskander, Taha Ali Mohammed (2011)
Brazil has been one of the significant recipients of foreign direct investment (FDI) among the newly emerging markets of global economy over the last 20 years, and has recorded rapid and sustained growth rates in a number of different industrial sectors. Indeed, FDI plays a significant role in the Brazilian economy. Brazil has been pursuing different foreign investment policies at different times depending on the development objectives and economic situation in the country. The present study has focussed on to empirically examine the influence of macroeconomic variables on Foreign Direct Investment in the Brazilian economy. The chosen macroeconomic variables are Gross Domestic Product (GDP), GDP per Capita (GDPPC), GDP growth rate(GDPGR), Trade ratio(TR), Exchange rate(ER), Inflation (INF) and rate of interest (Ri) as major determining factors. Regression method is applied to assess the functional relationship among these variables. The study is confined to the period of 20 years over 1990-2009 in Brazil. The findings of this study show that there is a strong positive relationship between Ex Rate, GDP, GDPPC and TR to the flow of FDI in the Brazilian economy.However, negative association between GDPGR, INF and Ri to FDI.